Biharmonic Maps into S-Space forms (European Journal of Pure and Applied Mathematics, 2018)
We study in this paper the condition on second fundamental form for biharmonicity of submanifolds in S-space forms.
Keywords: S-Manifolds; harmonic map; biharmonic maps